Astrocytes in Atp1a2‐deficient heterozygous mice exhibit hyperactivity after induction of cortical spreading depression. Issue 6 (23rd April 2020) - Sugimoto, Hiroki; Sato, Masaaki; Nakai, Junichi; Kawakami, Kiyoshi
Abstract : The ATP1A2 coding α2 subunit of Na, K‐ATPase, which is predominantly located in astrocytes, is a causative gene of familial hemiplegic migraine type 2 (FHM2). FHM2 model mice ( Atp1a2 tmCKwk/+ ) are susceptible to cortical spreading depression (CSD), which is profoundly related to migraine aura and headache. However, astrocytic properties during CSD have not been examined in FHM2 model mice. Using Atp1a2 tmCKwk/+ crossed with transgenic mice expressing G‐CaMP7 in cortical neurons and astrocytes ( Atp1a2 +/− ), we analyzed the changes in Ca 2+ concentrations during CSD. The propagation speed of Ca 2+ waves and the percentages of astrocytes with elevated Ca 2+ concentrations in Atp1a2 +/− were higher than those in wild‐type mice. Increased percentages of astrocytes with elevated Ca 2+ concentrations in Atp1a2 +/− may contribute to FHM2 pathophysiology. Abstract : Atp1a2 +/ − is a model mouse of familial hemiplegic migraine type 2. The numbers of astrocytes with elevated Ca 2+ concentrations in Atp1a2 +/ − (11.0 ± 2.8 astrocytes) were larger than those in wild‐type mice (5.7 ± 2.5 astrocytes) after induction of cortical spreading depression (which is closely associated with migraine) by application of KCl.